2000
DOI: 10.4049/jimmunol.165.6.3350
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane Form of the Type II IL-1 Receptor Accounts for Inhibitory Function

Abstract: IL-1 signaling is mediated by the type I IL-1R (IL-1RI). The nonsignaling type II receptor has a regulatory function, since it reduces IL-1 effects by scavenging free IL-1 molecules. This regulatory function has been demonstrated only for the soluble form, released from the membrane receptor by action of specific proteases, but is still ill-defined for the membrane receptor itself. To assess the function of membrane IL-1RII, a modified IL-1RII cDNA was constructed, in which the cleavable domain was replaced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 40 publications
(36 reference statements)
4
45
0
Order By: Relevance
“…It has recently been demonstrated that the membrane-bound form of IL-1RII is itself directly involved in the negative regulation of IL-1 (24) and that it acts as a dominant negative by forming a nonsignaling complex with the accessory protein (8,13,14). In the present study, we report that binding of IL-1 to membraneanchored IL-1RII causes internalization of the receptor-ligand complex, representing a further level of IL-1 autoregulation.…”
mentioning
confidence: 52%
“…It has recently been demonstrated that the membrane-bound form of IL-1RII is itself directly involved in the negative regulation of IL-1 (24) and that it acts as a dominant negative by forming a nonsignaling complex with the accessory protein (8,13,14). In the present study, we report that binding of IL-1 to membraneanchored IL-1RII causes internalization of the receptor-ligand complex, representing a further level of IL-1 autoregulation.…”
mentioning
confidence: 52%
“…IL-1 (IL-1Α and IL-1Β), a multifunctional cytokine involved in a host of pro-inflammatory responses and diseases [50], affects target cells through two distinct types of transmembrane receptors, IL1R1 and IL1R2. IL1R1 transduces the signal from IL-1, while IL1R2 acts as a decoy receptor to subtract IL-1 from ILR1 [51,52]. The ratio between the expression of IL1R1 and IL1R2 has been shown to be the central factor in determining the responsiveness of a cell to IL-1 [53].…”
Section: Discussionmentioning
confidence: 99%
“…The non-signaling type II IL-1 receptor (IL-1RII) is thought to function as a decoy receptor that inhibits cellular responses to IL-1 (Neumann et al, 2000). GC-induced upregulation of IL-1RII has been described in a number of studies (Brown et al, 1996;Colotta et al, 1993;Ehrchen et al, 2007;Pousset et al, 2001) and may contribute to inhibition of a very specific subset of (IL-1-mediated) inflammatory responses.…”
Section: Il-1 Receptor Type IImentioning
confidence: 99%